Modulating mitochondrial calcium channels (TRPM2/MCU/NCX) as a therapeutic strategy for neurodegenerative disorders - Johnson, Gretchen A.; Krishnamoorthy, Raghu R.; Stankowska, Dorota L. (Frontiers in Neuroscience, 2023)
Efficient cellular communication is essential for the brain to regulate diverse functions like muscle contractions, memory formation and recall, decision-making, and task execution. This communication is facilitated by rapid signaling through electrical and chemical messengers, including voltage-gated ion channels and neurotransmitters. These messengers elicit broad responses by propagating action potentials and mediating synaptic transmission. Calcium influx and efflux are essential for releasing neurotransmitters and regulating synaptic transmission. Mitochondria, which are involved in oxidative phosphorylation, and the energy generation process, also interact with the endoplasmic reticulum to store and regulate cytoplasmic calcium levels. The number, morphology, and distribution of mitochondria in different cell types vary based on energy demands. Mitochondrial damage can cause excess reactive oxygen species (ROS) generation. Mitophagy is a selective process that targets and degrades damaged mitochondria via autophagosome-lysosome fusion. Defects in mitophagy can lead to a buildup of ROS and cell death. Numerous studies have attempted to characterize the relationship between mitochondrial dysfunction and calcium dysregulation in neurodegenerative diseases such as Alzheimer's Disease, Parkinson's Disease, Huntington's Disease, Amyotrophic lateral sclerosis, spinocerebellar ataxia, and aging. Interventional strategies to reduce mitochondrial damage and accumulation could serve as a therapeutic target, but further research is needed to unravel this potential. This review offers an overview of calcium signaling related to mitochondria in various neuronal cells. It critically examines recent findings, exploring the potential roles that mitochondrial dysfunction might play in multiple neurodegenerative diseases and aging. Furthermore, the review identifies existing gaps in knowledge to guide the direction of future research.